(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
This research revolves around explaining the conceptual, textual and historical importance of interpretation, and presenting a new classification of Muslims and Islamic thinkers. Accordingly, the research consists of two main sections, the first of which is devoted to reviewing the concept of interpretation linguistically and terminologically, then presenting the position and importance of interpretation in the Qur’anic and Prophetic textual sources, then among some of the Prophet’s companions and followers, leading to the historical importance of interpretation. The second topic revolves around the interpretive currents in Islamic thought, as we found that they are divided into two currents: a textual current, and an interpretive current. We have divided the textual current into two directions: a definitive textualist that rejects interpretation in a definitive manner, and an interpretive textualist that acknowledges interpretation but limits it to clarification and interpretation. As for the interpretive current, it is also divided into two directions: a rational interpretive, which acknowledges interpretation and evaluates it on conditions, the most important of which are: language and reason, and a mystical textual, which evaluates interpretation on the basis of gnosis or mysticism. The research has concluded with a set of results, the most important of which are: 1. There is a textual and historical preference for interpretation over interpretation. 2. The definitive textual trend stands in contrast to the mystical hermeneutic trend.